Advanced medical imaging technique in endodontics: a literature review - บุญทวี พีรยา; ปัญญารักษ์ วรรณกมล; ศรีสุวรรณ ธนิดา (Thai Endodontic Journal, 2022)
Radiographic examination plays an important role in root canal treatment procedures. It is a useful tool for diagnosis, treatment planning, intra-operative control and outcome assessment. The most common radiographic examination in endodontic field is an intraoral periapical radiograph. The radiograph provides root canal anatomy, periapical area and crucial surrounding anatomical structures. Although it is practical and does not require specialist for interpretation, periapical image has limitations of usage such as compression of three-dimensional anatomy, geometric distortion, anatomical noise and temporal perspective. The assessment from only conventional radiograph might have been misleading or difficult in some cases. This review explains the limitations of periapical radiograph and recommends the others advance medical imaging technique which had been recently used in endodontic field to overcome some of limitations association with periapical radiograph. These include ultrasound, computed tomography and cone beam computed tomography (CBCT) and magnetic resonance imaging (MRI). However, the intraoral periapical radiograph is still a proper image for initial assessment. Worthiness, necessity and safety should be considered for application of others advance technique.